Employee Organizational Commitment Towards Quality Outcomes: A Study in Manufacturing Organization of Nepal - Basnet, Bhupindra Jung (Pravaha, 2020)
The purpose of this paper is to examine the impact of total quality management practices on employees’ organizational commitment in Nepalese manufacturing industry. Structural questionnaire are used. Data was analyzed by employing correlation and sample regression analysis. The result of this study revealed that training and education, teamwork, and organizational culture are positively associated with employees’ organizational commitment.